CHARACTERISTICS AND TREATMENT OF COAGULOPATHY ASSOCIATED WITH COVID-19 - Miljić, Predrag (Medicinski podmladak, 2021)
Coagulopathy in COVID-19 represents a thrombo-inflammatory condition, and it is one of the most important causes of morbidity and mortality in this disease. The occurrence of coagulopathy correlates with the intensity of the inflammatory response to SARS-Cov-2 virus infection, and its presence is characterized by laboratory markers of blood hypercoagulability and clinically pronounced prothrombotic condition. Although the mechanism of coagulopathy is not fully elucidated, dysregulated and overemphasized immune responses mediated by inflammatory cytokines, complement activation, leukocyte activation with release of free nucleic acids and histones into the circulation, hypoxia and endothelial damage play a very important role in its development. Thrombosis can occur in all parts of the circulatory system and is most often localized in the microcirculation and venous part of the vasculature. A number of studies have shown that the presence of thrombotic pulmonary embolism can be demonstrated by objective methods in approximately 15% of COVID-19 patients treated in intensive care units, while the incidence of total venous thromboembolism in this group of patients is over 20% despite antithrombotic prophylaxis. Although much less common than venous thrombosis, arterial thrombosis may also occur in COVID-19 patients, most often in the form of myocardial infarction, ischemic stroke and peripheral artery occlusion. Damage to the endothelium under the influence of virus or inflammatory response, activation of platelets and coagulation system with fibrin deposition leads to extensive thrombosis in the microcirculation of lungs and other tissues and directly contributes to respiratory failure, ARDS or multiorgan failure. Therefore, coagulopathy in COVID-19 is an integral part of the pathophysiological mechanism of the disease and contributes to its clinical manifestation and progression. The main laboratory characteristics of COVID-19 coagulopathy are elevated values ​​of D-dimer in the blood, which occurs in the process of decomposition of precipitated fibrin under the action of fibrinolytic enzymes in the microcirculation of the lungs and other organs. Therefore, D-dimer values ​​reflect the intensity of the inflammation in the lungs and have prognostic significance in recognizing patients at risk of serious complications and unfavorable course of the disease. In contrast to disseminated intravascular coagulation in sepsis, severe thrombocytopenia and hypofibrinogenemia as well as bleeding tendencies are rare in COVID-19 coagulopathy. Due to the high frequency and important role of coagulopathy in morbidity and mortality, the use of anticoagulant therapy is recommended in all hospitalized patients. However, the optimal way of treating coagulopathy and the intensity of antithrombotic prophylaxis are not known, and represent the subject of intensive research.